New Insights in Candida albicans Innate Immunity at the Mucosa: Toxins, Epithelium, Metabolism, and Beyond - Pellon, Aize; Sadeghi Nasab, Shervin Dokht; Moyes, David L. (Frontiers in Cellular and Infection Microbiology, 2020)
The mucosal surfaces of the human body are challenged by millions of microbes on a daily basis. Co-evolution with these microbes has led to the development of plastic mechanisms in both host and microorganisms that regulate the balance between preserving beneficial microbes and clearing pathogens. Candida albicans is a fungal pathobiont present in most healthy individuals that, under certain circumstances, can become pathogenic and cause everything from mild mucosal infections to life-threatening systemic diseases. As an essential part of the innate immunity in mucosae, epithelial cells elaborate complex immune responses that discriminate between commensal and pathogenic microbes, including C. albicans. Recently, several significant advances have been made identifying new pieces in the puzzle of host-microbe interactions. This review will summarize these advances in the context of our current knowledge of anti-Candida mucosal immunity, and their impact on epithelial immune responses to this fungal pathogen.